2019
DOI: 10.7567/1347-4065/ab4003
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked Tm-doped fiber laser with large modulation depth ReS1.02Se0.98 nanosheet saturable absorber

Abstract: In this paper, we demonstrate excellent ultrafast optical performance of ternary transition metal dichalcogenide ReS1.02Se0.98 saturable absorber with high power tolerance and large modulation depth in thulium-doped fiber laser. Q-switching with tunable repetition frequency and pulse duration, and mode-locking with high pulse energy were generated in our experiment. The average output power/pulse energy/pulse duration of the mode-locked pulse train were 313 mW/13.6 nJ/1.43 ps, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Then, we used ReS 1.02 Se 0.98 SA to realize a self-starting noise-like mode-locked pulse at 1 μm [37]. At the same time, the mode-locked pulse with extremely high output power is realized by using ReS 1.02 Se 0.98 SA in a Tm-doped fiber laser [38]. These confirmed the possibility of this new ternary TMD alloy to modulate pulse in a wide wavelength range.…”
Section: Introductionsupporting
confidence: 52%
“…Then, we used ReS 1.02 Se 0.98 SA to realize a self-starting noise-like mode-locked pulse at 1 μm [37]. At the same time, the mode-locked pulse with extremely high output power is realized by using ReS 1.02 Se 0.98 SA in a Tm-doped fiber laser [38]. These confirmed the possibility of this new ternary TMD alloy to modulate pulse in a wide wavelength range.…”
Section: Introductionsupporting
confidence: 52%
“…The pulse duration of 67 fs by using WS 2 as the SA in EDFL (Fig. 14), 275 the average output power of 313 mW at 1924 nm with ReS 1.02 Se 0.98 as the SA in the mode-locked TDFL, 41 and the repetition rate of 3.27 GHz at 1557.3 nm with MoSe 2 as the SA in mode-locked EDFL 255 were obtained. In addition to TMDs, other chalcogenides-based 2DLMs such as In 2 S 3 , 276 In 2 Se 3 , 277 InSe, 278 GaS, 279 GaSe, 280 SnS, 281 TiS 3 , 282 and Ta 2 NiS 5 283 were also employed as the SAs.…”
Section: Applications Of Emerging Nanostructured Materials As the Sas...mentioning
confidence: 98%
“…36 Huang and coworkers reported a contamination-free and universal mechanical exfoliation method for 40 types of large-area single-layer 2DLMs. 37 By using the mechanical exfoliation method, 2DLMs such as graphene, 33 TIs, 38,39 TMDCs, 40,41 and BP 18,42 have been obtained. The obtained 2DLMs can have a relatively large lateral size, high crystallinity and fewer defects.…”
Section: Preparation Of Emerging Nanostructured Materialsmentioning
confidence: 99%
“…15) In 2019, Zhang et al demonstrated that the modulation depth of the ternary alloy ReS 1.02 Se 0.98 is as high as 39.9% at 2 μm, which is much higher than ReSe 2 (7.3%) and ReS 2 (3.9%), and it is used as a SA to the generation of ultrafast lasers by passively mode-locked technology at 2 μm. 11,21,22) These works have the significance to promote the application of ternary alloy materials in pulsed lasers as SAs. Comparing with traditional TMDs, TMDs alloys possess better optoelectronic properties, which is interesting to explore novel TMDs alloy materials and optoelectronic devices.…”
mentioning
confidence: 99%